Sturge-Weber Syndrome: A comprehensive review of clinical features, optimized diagnosis and management strategies - Naja, Katarzyna; Kapciak, Alicja; Górny, Julia; Świerzyńska, Adrianna; Hawajski, Artur; Jankowska, Natalia; Kamieniecka, Oliwia; Zwardoń, Jakub; Mazur, Weronika; Pawelec, Natalia (Quality in Sport, 2024)
Introduction: Sturge-Weber Syndrome is a rare neurocutaneous disorder characterized by facial port-wine birthmarks, leptomeningeal angiomatosis, and associated neurological, ophthalmological, and dermatological symptoms. The condition's variable presentation poses challenges for diagnosis, management, and long-term care. Advances in imaging, genetics, and targeted therapies are reshaping the landscape of Sturge-Weber Syndrome treatment. Aim of Study: This review aims to summarize current knowledge on the clinical manifestations, diagnostic approaches, differential diagnoses, and treatment options for Sturge-Weber Syndrome, with a focus on the management of neurological, ophthalmological, and dermatological symptoms. Material and methods: A comprehensive review of the literature on Sturge-Weber Syndrome was performed using the PubMed database. Results and Conclusions: Sturge-Weber Syndrome is a complex disorder requiring a multidisciplinary approach to management. Neurological complications, particularly epilepsy, are a major concern, often necessitating pharmacological or surgical interventions. Ophthalmological issues, especially glaucoma, pose challenges across all age groups, with tailored treatments offering varying success. Dermatological symptoms, such as port-wine stains, benefit significantly from early pulsed dye laser therapy, often enhanced by adjunctive treatments like topical rapamycin. Emerging therapies, including sirolimus and aspirin, show promise in reducing complications. Advances in imaging techniques and targeted treatments offer hope for improved management, while lifelong monitoring remains essential. Further research into the pathophysiology and therapies for Sturge-Weber Syndrome is critical to developing personalized and effective treatment strategies, ultimately improving patient outcomes.